The Need Analysis of Learning Module Development Using Self Organized Learning Environment (Sole) Assisted by Augmented Reality on Rotational Dynamics and Rigid Body Equilibrium - Oktaviyani Rosniadi Pratama; Connie Connie; Eko Risdianto (Universitas Bengkulu, 2021)
This study aims to analyze the need for the development of learning module using the Self Organized Learning Environment (SOLE) model assisted by Augmented Reality on rotational dynamics and rigid body equilibrium. This type of research is a survey research and literature study which later can be the basis for further development research. The research instrument used was a needs analysis questionnaire with 20 questions given to 72 respondents who were students and 3 respondents who were teachers of class XI MIPA from SMA Negeri 5 Bengkulu City, SMA Negeri 4 Bengkulu City and SMA Negeri 9 Bengkulu City. In this research the data analysis uses descriptive statistics. Based on the results of the data obtained it can be concluded that currently students are in dire need of computer-based learning media, one of which is by using Augmented Reality. This is based on data obtained that 76,26 % of students answered Strongly Agree and 77,92 % of teachers answered Strongly Agree to the need for the development of the development of learning module using the Self Organized Learning Environment (SOLE) model assisted by Augmented Reality on rotational dynamics and rigid body equilibrium. We know that the development of digital technology in the current Industrial 4.0 era has brought changes and influenced various aspects of human life, including in the field of education. Augmented Reality are technologies that can be developed to provide alternative instructional media provided previously and to see the effectiveness of these media if used in learning activities.